Three new species of the subfamily Cladonotinae (Orthoptera: Tetrigidae) from Thailand - Storozhenko, Sergey Yu.; Dawwrueng, Pattarawich (Zootaxa, 2014)
The pygmy grasshopper subfamily Cladonotinae and genera Epitettix Hancock, 1907, Pseudepitettix Zheng, 1995 and Tuberfemurus Zheng, 1992 are firstly recorded from Thailand. Three new species, namely Epitettixobtusus obtusus sp. nov. from provinces Nakhon Ratchasima and Chiang Mai, Pseudepitettix pimkarnae sp. nov. from province Saraburi and Tuberfemurus kanokwanae sp. nov. from province Saraburi, are described.